DISREGARD OF THE CORPORATE ENTITY IN RUSSIAN CASE LAW - Irina Ivanovna Baukina (International Journal of Law in Changing World)
This paper reviews the legal doctrines developed in case law and used to challenge corporate decisions and resulting transactions: the doctrine of piercing the corporate veil, the beneficial ownership doctrine, affiliation, and corporate estoppel. When applied, these doctrines strip the entity of its incorporated status and separate existence. The article observes that the doctrines under discussion are used to stop abuse by managers and directors in corporate contexts. The author concludes that, where affiliated, an entity does not hide behind the corporate veil, as is the case in the doctrine of lifting the corporate veil, but exercises corporate control openly. Also, the beneficial ownership doctrine is applicable when an entity holds equity interests not directly but through a chain of affiliated companies and trusts. The following circumstances can provide grounds for applying this type of estoppel to challenge a corporate decision: non-compliance with corporate customs and standard forms of the documents recording the decision-making process; non-compliance with the time-honored procedure for corporate discussion and decision-making; a person was deceived into thinking that they were dealing with a company, whereas it was a citizen, and vice versa.